Estimulao ambiental e prontidao - Witter, Geraldina Porto (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
This article considers and reviews the relationship between readiness and environmental stimulation. It finds that both environmental stimulation and prior learning are significant variables in subsequent learning. While psychologists are largely in agreement on this topic, this article sees a need for the evolvement of materials and programs specifically designed to facilitate readiness development.